The Half-Sweep Iterative Alternating Decomposition Explicit (HSIADE) method for diffusion equation - Sulaiman, Jumat; Hasan, Mohammad Khatim; Othman, Mohamed (Springer, 2004)
The primary goal of this paper is to apply the Half-Sweep Iterative Alternating Decomposition Explicit (HSIADE) method for solving one-dimensional diffusion problems. The formulation of the HSIADE method is also derived. Some numerical experiments are conducted that to verify the HSIADE method is more efficient than the Full-Sweep method